Emergency obstetric hysterectomy: a lifesaving procedure - Doddamani, Usha; Rampure, Nirmala; Kulkarni, Sanyogita; Patil, Shoba; Tambre, Neelavati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency Obstetric Hysterectomy (EOH) is removal of uterus following vaginal delivery, Emergency LSCS or within the puerperium period. Because of increasing caesarean deliveries, the number of scarred uterus is increasing exposing the gravid women to increasing morbidity from uterine rupture, placenta accrete and placenta previa thus increasing the incidence of Emergency obstetric hysterectomy. The aim was to determine the incidence, demographic details, high risk factors and fetomaternal outcome of patients who underwent EOH. Methods: This was a retrospective study where data was collected from the record sheets of patients who underwent Emergency Obstetric Hysterectomy from January 2016 to December 2017 in the department of OBG, GIMS Gulbarga. Maternal age, parity, socioeconomic status, antenatal care, high risk factors and fetomaternal outcome were analysed. Results: During the study period there were 17,820 deliveries out of which 20 cases underwent EOH giving an incidence of 0.12%. Most of patients were uneducated, unbooked, low SES and of rural background and were multiparous. Main cause for EOH were rupture uterus, PPH and morbidly adherent placenta. There were 2 cases of maternal mortality and fetal mortality was 65%. Conclusions: Though EOH is a lifesaving procedure it curtails the reproductive capacity of the women. Proper antenatal care, early referral, timely decision and skill of surgeon in performing this procedure is important.